Execution, state and society in England, 1660-1900 - Devereaux, Simon Paul Ross (Studies in legal history, 2023)
"This book charts the history of execution laws and practices in the era of the "Bloody Code" and their extraordinary transformation by 1900. Innovative and comprehensive, this work will find an audience with scholars interested in the history of crime and punishment in England"